SISTEM PENDUKUNG KEPUTUSAN SELEKSI CALON KETUA OSIS BERBASIS WEBSITE MENGGUNAKAN METODE AHP (ANALYTICAL HIERARCHY PROCESS) - Anifathul Mufidha , Arinda; Mufarrihah , Iftitaahul (Inovate, 2024)
The Student Council (Organisasi Siswa Intra Sekolah or OSIS) is an organization present in schools in Indonesia, starting from Junior High School (SMP) to Senior High School (SMA). The current selection process for the OSIS president candidate at Bintang Sembilan Vocational High School is still manual and involved several selection stages. The AHP method in this decision support system helps reduce subjectivity and improve accuracy in the selection process of OSIS president candidates at Bintang Sembilan Vocational High School. The AHP method also aims to assist in choosing the best candidate based on predetermined criteria. The research results have produced a web-based application that provides accurate final calculation results or rankings. The consistency ratio generated by the system is 0.097, indicating that the calculations performed are acceptable because the level of validity is sufficiently consistent. Based on the AHP method calculation results, candidates who meet the expected criteria have been identified. Kholik Muzaki obtained a score of 0.359116, Isrohin obtained a score of 0.278901, Miftahur Rozaq obtained a score of 0.17243, Riski Tri Amelia obtained a score of 0.120182, and Fitri Noviana obtained a score of 0.0693724. Keywords: Decision Support System, Analytical Hierarchy Process, The president of student council, Web.